Normative Nasalance Values in Vietnamese With Southern Dialect: Vowel and Tone Effects. - Duc Minh Nguyen; Lee, Sue Ann S.; Toko Hayakawa; Masahiko Yamamoto; Nagato Natsume (Journal of Speech, Language & Hearing Research, 2021)
Purpose: The purpose of the current study was to examine normative nasalance values in Vietnamese adult speakers with Southern dialect and to investigate the effects of vowels and tones on nasalance. Previous studies examining nasalance have been mainly conducted with Indo-European languages. Limited information on nasalance is available in tone languages other than Chinese. Furthermore, tone and vowel effects on nasalance scores in tone languages have not been fully examined. Method: Nasalance scores of various speech stimuli including passages, syllables, and prolonged vowels were obtained from Vietnamese-speaking adults with Southern dialect (Mage = 23 years) using a nasometer (KayPENTAX 6450). Results: The average nasalance scores of Southern Vietnamese adult speakers were 24.16%, 38.17%, and 70.03% for the oral, oral-nasal, and nasal passages, respectively. Southern Vietnamese speakers produced the highest nasalance scores on the vowel /a/, followed by /i/ and /u/. Nasalance scores of stimuli produced with the falling and restricted tone were significantly lower than those produced with the other tones. Conclusions: The normative nasalance values of the current study will contribute as a reference index for the Vietnamese language. The effects of vowels and tones can also provide insight into the development of nasalance testing stimuli and for characterizing nasalance values across languages.